Quality of life assessment tools for chronic cough in children: a systematic review - Cao, Bingxue; Wang, Tianhan; Zhai, Siming; Zhang, Sha; Yuan, Bin (Frontiers in Public Health, 2025)
PurposeThe aim is to examine studies evaluating the life quality of children suffering from chronic cough over the last 10 years, concentrating on three areas: the development and validation of new tools, the cultural adaptation of existing tools, and the usage of common tools.MethodsA series of digital explorations were conducted in PubMed, Web of Science, EMBASE, and the Cochrane Library databases to find pertinent literature. The selection of literature adhered to specific criteria for its inclusion and exclusion. Analytical methods are documented in the International Prospective Register of Systematic Reviews, identified by the registration number CRD42024583481.ResultsOur collection encompassed 3,186 records, culminating in the inclusion of 14 studies. One study concentrated on the development and validation of a new assessment tool. The study evaluated the dependability, accuracy, and responsiveness of the child cough specific quality of life questionnaire (CC-QoL), but the number of participants was notably small. Research focusing on the creation and verification of localized language editions of current tools was absent. Thirteen studies, predominantly from China and Australia, employed quality of life (QoL) evaluation instruments as the outcome metrics. Chinese studies employed a wide range of evaluation instruments. Research in Australia employed the parent cough specific quality of life questionnaire (PC-QoL).ConclusionOver the last 10 years, minimal research has been conducted on the creation, application, and cultural modification of QoL evaluation instruments for chronic cough in children.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024583481.